(3GJMGa GdSGdc HQhGI ehWC eGdcs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3eMeO Hf eMeO Hf CHj MGeO Hf MSjf Hf Ydi GdeGdci GdHcQi GdNdjdi s)
(3ChdgG (B:s
(3hHYO aEf HYV Cgd GdSfI hNOGegG hef fTC Hjf GjeJgG hGYdGegG s
(3BNQgG (B:s
(3CHh MPGaI gPG BNQ GdQhGI dehWC eGdc MSHeG fXefGg hJCNQ ajeG GYde Yf PcQfG ai GdhaGI , hHJeGe PcQg fLR EJMGa GdSGdc HQhGI GdehWC Yf eGdc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B81 - (3U(B158s
(3cJHJ fbdkG Yf fSNI GdeDdas
(3QhGjI CHj GdNjQ eMeO bWH GdOjf GdNjVQi ef eDdag eTGagI HGdELGRI PcQ ajg QhGI ehWC eGdc GdPjf dbhg hSeYhG cJGHg GdehWC efgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
Keywords: (3GdJGQjNs